مستوى الوعي ما وراء المعرفي وعلاقته بحل المشكلات لدى طلاب الصف العاشر - الحوري، عبدالله; التل، شادية أحمد (جامعة إربد الأهلية - عمادة البحث العلمي, 2021)
هدفت الدراسة إلى معرفة مستوى الوعي ما وراء المعرفي لدى طلاب الصف العاشر وعلاقته بحل المشكلات. ولتحقيق أهداف الدراسة، قام الباحثان بتطوير مقياس الوعي ما وراء المعرفي (Schraw and Dennison, 1994)، ومقياس حل المشكلات (Barkman & Machtmes, 2002)، وتطبيقهما على عينة مكونة من (200) طالب. وقد أظهرت النتائج الدراسة أن مستوى الوعي ما وراء المعرفي لدى طلاب الصف العاشر جاء بدرجة "مرتفعة". كما أظهرت نتائج الدراسة وجود علاقة ارتباطية إيجابية قوية دالة إحصائياً بين الوعي ما وراء المعرفي وحل المشكلات لدى طلاب الصف العاشر. كما كشفت النتائج أن المتغير المتنبأ (الوعي ما وراء المعرفة)، والمتغير المتنبأ به حل المشكلات لدى طلاب الصف العاشر قد كان دالاً إحصائيا (α= 0.05) بأثر مشترك ونسبي للمتغير المتنبأ الوعي ما وراء المعرفي، مفسراً ما مقداره (54%) من التباين المفسر الكلي للنموذج التنبؤي. وتبين أنه كلما زاد الوعي ما وراء المعرفي ببعد دال (المعرفة حول المعرفة) وبعد دال (تنظيم المعرفة) بمقدار وحدة معيارية، فإن حل المشكلات لدى طلاب يزداد بمقدار (73.3%). مما يدل على وجود علاقة خطية طردية "موجبة القيمة" بين الوعي ما وراء المعرفي وحل المشكلات لدى طلاب الصف العاشر. The study aimed to Know the metacognitive Awareness Level Among Tenth Grade Students and its Relationship to Problem Solving. To achieve the objectives of the study, the researchers developed the Metacognitive Awareness Scale (Schraw& Dennison, 1994), Problem Solving Scale (Barkman& Machtmes, 2002), And applied to a sample of (200) students. They were selected Available sample and after checking the validity and reliability of the tools, they were applied to the study sample. The results of the study indicated that the level of Metacognitive Awareness in the Tenth-Grade student was "High". The results showed a statistically significant positive correlation between Metacognitive Awareness and Problem Solving for the Tenth-Grade students. The results showed a moderate significant correlative between Metacognitive Awareness and Self-Organization for the Tenth-Grade students. The results also indicated that the predictive variable of the metacognitive awareness, and the predictive variable of the problem solving for the tenth-grade students was statically significant (α=0.05) with a rational and common effect for the metacognitive awareness predictive variable, explaining the percentage of (54%) of the overall explanatory variation of the predictive model. It was showed that the greater the metacognitive awareness (Knowledge about Knowledge) and (Knowledge organization) by a standard unit, the Problem Solving the tenth-grade students increases by (73.3%) which indicates a linear correlation " positive value" between Metacognitive Awareness and Problem Solving for the Tenth-Grade students.
Keywords: العمليات المعرفية -- الإبداع العقلي -- المهارات المعرفية -- التعلم الذاتي -- طلبة المرحلة المتوسطة